2018
DOI: 10.3389/fvets.2018.00053
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia-Associated Relative Hypovolemia: Mechanisms, Monitoring, and Treatment Considerations

Abstract: Although the utility and benefits of anesthesia and analgesia are irrefutable, their practice is not void of risks. Almost all drugs that produce anesthesia endanger cardiovascular stability by producing dose-dependent impairment of cardiac function, vascular reactivity, and compensatory autoregulatory responses. Whereas anesthesia-related depression of cardiac performance and arterial vasodilation are well recognized adverse effects contributing to anesthetic risk, far less emphasis has been placed on effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 217 publications
(254 reference statements)
0
30
0
2
Order By: Relevance
“…A reduction in total circulating blood volume. Absolute hypovolemia can be caused by dehydration (i.e., water and electrolyte loss) or the loss of blood from the body or into a body cavity (e.g., abdomen) ( 1 , 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in total circulating blood volume. Absolute hypovolemia can be caused by dehydration (i.e., water and electrolyte loss) or the loss of blood from the body or into a body cavity (e.g., abdomen) ( 1 , 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…With active rewarming measures, it is a possibility that the subsequent vasodilatation caused could have unmasked an underlying hypovolemia which further exacerbated the hemodynamic instability [15]. Relative hypovolemia caused due to vasodilatation primarily, venodilation, encountered during anesthesia has been attributed to multiple factors, such as the effect of anesthetic agents, loss of compensatory mechanisms, metabolic or respiratory acidosis, traumatic or surgically mediated inflammation and sepsis [16]. Kim et al in their study showed an increase in one year mortality in post-operative patients having an increase or decrease in axillary temperatures (taking median temperature as 36.6 degree Celsius) on admission to the ICU [17].…”
Section: Discussionmentioning
confidence: 99%
“…Si bien esta última definición es útil, ya que acepta el término de SBGC en pacientes en los que no conocemos el GC, (muy frecuente en la práctica clínica habitual) incluye el concepto de "hipovolemia relativa". Según la literatura, esta se define como la incapacidad del volumen sanguíneo de llenar el compartimiento vascular por disminución de las resistencias vasculares sistémicas (RVS) (7,8) . Sin embargo, la definición de la SEMICYUC se refiere a una PCP <15 mmHg.…”
Section: Definiciónunclassified